Study of ultra wideband bandpass filter using electromagnetic simulator - Devkumar S.; Chakrabarty C.K.; Hock G.C.; Badjian M.H.; Emmiliano (2023)
An ultrawideband composite microstrip bandpass filter is designed using electromagnetic (EM) structure simulation. The design utilizes embedding individually designed highpass and lowpass filter (LPF) onto each other on a FR-4 board. The stepped-impedance LPF is employed to attenuate the upper stopband where as short-circuited stubs are used to realize the lower stopband. The results are analyzed in terms of the insertion loss, return loss, overall group delay and also the input and output signals. EM structure simulation is done using CST (Microwave Studio). Fabrication and measurements are done to conduct comparative studies between the simulated results and the measured results. 2008 IEEE.